Reducing the residual error of multibeam sounding data through empirical mode decomposition based on cubic Bessel interpolation. (April 2021) - Sun, Jialong; Zhang, Zhengyang; Zhang, Chi; Liu, Jinlei; Zhang, Peng
The systematic residual errors present in multibeam echo-sounding data cause the areas of overlap between adjacent swaths to become distorted. A method is proposed in this paper to reduce the residual error of multibeam sounding data through empirical mode decomposition (EMD) based on cubic Bessel interpolation. Numerical experiments confirm that the discrepancy in the overlap between two swaths is significantly reduced after applying EMD improved by cubic Bessel interpolation compared with both the original water depth data and with data processed using conventional EMD based on cubic spline interpolation. The mean square error of the improved method is decreased by 67% and 29% compared with that of the original and conventional EMD cases, respectively. Therefore, EMD with cubic Bessel interpolation can efficiently reduce the residual error of multibeam echo-sounding data.